Money, banking and financial markets - Cecchetti, Stephen G. (Stephen Giovanni); Schoenholtz, Kermit L (Dubuque, IA McGraw Hill Education, 2024)
"Preface The world of money, banking, and financial markets is constantly evolving. Every year, people ex-plore new ways to pay for purchases, save for the future, and borrow to meet current needs. New technology is an ongoing source of change. Internet banking makes it easier than ever for individuals to take control of their finances. And smartphones not only allow American college stu-dents to pay for their morning coffee but also are giving hundreds of millions of people in poor countries their first access to the financial system. In some instances, crises provided the impetus for change. For example, new regulations aimed at making the financial system safer have pushed many banks to take fewer risks than they did just a few years ago. Financial markets also have become more resilient and less likely to need public support. And monetary policymakers, especially in places where economic growth has slowed and deflation is a risk, have adopted a slew of policies never seen before. In much of Europe and Japan, interest rates have fallen below zero-breaking through what had long been seen as a permanent -barrier-while new policies are in place to boost bank lending and restore inflation and growth to precrisis levels"--
Includes index.
Keywords: Banks and banking; Capital market; Finance; Money